PENGARUH MODEL CIRC (COOPERATIVE INTEGRATED READING AND COMPOSITION) DENGAN MENGGUNAKAN PETA KONSEP TERHADAP HASIL BELAJAR SISWA PADA MATERI JARINGAN TUMBUHAN DI KELAS XI IPA SMA MUHAMMADIYAH 1 MEDAN - Chantria Novita Syaputri; Ely Djulia (Jurnal Pelita Pendidikan, 2018)
This study aims to determine the effect of CIRC learning model with concept map on student learning outcomes on plant tissue material in class XI IPA SMA Muhammadiyah 1 Medan T.P.2017 / 2018. This research type is quasi experiment with research population of all class XI IPA SMA Muhammadiyah 1 Medan consists of 2 classes. The sample of this research is selected by using technique of Total Sampling. The instrument used in this study is the test in the form of objective tests, which are as many as 25 questions that each have been declared valid and reliable. Based on the data requirement test, it is known that the research data is normally distributed and the two classes have the same variance (homogeneous). From the data analysis it is known that the mean score of postes of students who were taught with CIRC was 84.12 and the mean score of postes of students who were taught with CIRC using concept map was 90.06. There is a significant difference on student learning outcomes, it is proved by t-test at significant level α = 0,05 and dk 62 obtained tcount> ttable (3,079> 1,999) hence this research reject Ho and accept Ha. Thus, it can be concluded that there is influence of student learning outcomes taught by CIRC learning model using Concept Map on Plant Network material In Class XI IPA SMA Muhammadiyah 1 Medan T.P. 2017/2018.Keywords: CIRC, CIRCusing concept map, the results of the study.